Stories from Asia today : a collection for young readers - Asian Cultural Centre for Unesco." (New York : Weatherhill/Heibonsha, 1979)
A collection of contemporary short stories from Asian countries.
"Sponsored by Asian Cultural Centre for Unesco."
Keywords: Children's stories, Oriental -- Translations into English; Short stories; Asia -- Fiction